Policing in America: Abolish or Amerliorate - St. Clair, Zachary (Kansas State University. K-State Libraries, 2018)
This paper offers an exploration into the world of American police abolition and police reform. Through perspectives of community groups, criminology scholars and theorists, as well as criminological data, this paper presents a history of policing in America, an argument of the necessity of action in the realm of police reform or abolition, as well as a selection of possible policing alternatives which are in use across America currently. Sources for this work were compiled through various search engines within and outside of K-State Libraries, as well as through the use of K-State Libraries’ Interlibrary Loan. Featured texts range from leading books in the field of criminology, to the work of activist groups, to data compiled by the U.S. Government, to more culturally and less-academically oriented texts such as various reporting features and interviews.
Citation: St. Clair, Z. (2018) Policing in America: Abolish or Amerliorate. Unpublished manuscript, Kansas State University, Manhattan, KS.
Kirmser Undergraduate Research Award - Individual Non-Freshman Category, honorable mention